2018
DOI: 10.17925/ee.2018.14.2.67
|View full text |Cite
|
Sign up to set email alerts
|

Male Central Hypogonadism in Paediatrics – the Relevance of Follicle-stimulating Hormone and Sertoli Cell Markers

Abstract: The definition of male hypogonadism, used in adult endocrinology, is not fully applicable to paediatrics. A clear understanding of the developmental physiology of the hypothalamic-pituitary-testicular axis is essential for the comprehension of the pathogenesis of hypogonadal states in boys and for the establishment of adequate definitions and classifications in paediatric ages. This is particularly true for central hypogonadism, usually called hypogonadotropic in adults. Because childhood is a period character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 55 publications
0
21
0
2
Order By: Relevance
“…The mean increase in testosterone levels was 302.12 AE 180. 23 Cut-off values calculated for AMH and hCG responses in the groups are provided in Table 3. Patients with GD had lower AMH values than patients with AIS (P < 0.001).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The mean increase in testosterone levels was 302.12 AE 180. 23 Cut-off values calculated for AMH and hCG responses in the groups are provided in Table 3. Patients with GD had lower AMH values than patients with AIS (P < 0.001).…”
Section: Resultsmentioning
confidence: 99%
“…It is also reported that the serum AMH values are useful in the differential diagnosis of HHG and CDP . While AMH is low in HHG patients due to the lack of FSH stimulation, it is normal in delayed puberty patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although basal AMH production is not dependent on gonadotropins [32], FSH stimulates testicular AMH secretion [26,[33][34][35]. In turn, increased testosterone concentrations inhibit AMH secretion [18,36].…”
Section: Testosteronementioning
confidence: 99%
“…Another intriguing finding was that the Lz-treated boys had larger testes 6 months after the treatment than those who received low-dose T, although the iB levels did not differ at that time point (Varimo et al, 2019). To better understand the putative effects of Lz and low-dose T on the developing seminiferous epithelium, we now report serum levels of anti-Müllerian hormone (AMH), which is another Sertoli cell product and a suggested surrogate marker for Sertoli cell number and function (Grinspon et al, 2018). It is known that FSH stimulates AMH secretion in prepuberty (Lukas-Croisier et al, 2003;Young et al, 2005), and that the paracrine action of T suppresses AMH levels in early puberty (Rey, 1998).…”
Section: Introductionmentioning
confidence: 99%